Untersuchungen zur floristisch-pflanzengeographischen Differenzierung des Xizang-Plateaus (Tibet), China - Du, Zheng (ERDKUNDE, 1983)
The geo-ecological conditions of Xizang (Tibet) are very complicated, and the horizontal zonation of vegetation is closely correlated with the vertical. The horizontal differentiation of the geo-ecological zones is mainly determined by topographic configuration and atmospheric circulation: Warm and humid in the southeast, cold and arid in the northwest. The natural landscapes appear in the following succession: forests-meadows-steppes-deserts. An approach to the floristic phytogeographical differentiation of the study area has been made in the present paper with the help of a quantitative floristic method. According to the areal types of the species the flora of Xizang may be classified under five major geo elements: the north temperate zone geo-element (N), the Central Asiatic geo-element (Z), the Tibetan geo-element (T), the Sino Himalaya geo-element (SH) and the tropical geo-element (Tr). A brief outline of them has been presented with regard to their distribution areas and the significance in vegetation, with some examples of the characteristic species. The map of the spectra of floristic elements of Xizang (Tibet) in a grid-square system is presented with the paper. Five profiles were chosen to illustrate the spatial differentiation of the spectra of floristic elements of Tibet. Profiles A, B and C follow a nearly south north direction, profiles D and E are cross-sections nearly east-west orientated. The spatial differentiation of the main floristic elements of the study area is obvious: the SH-geo-element prevails in the eastern and south-eastern Tibet, and the Tr-geo-element is confined at the lower elevation of the southern flanks of the Himalayas. On the contrary, on the Plateau proper the T-geo-element dominates, and the Central Asiatic geo-element (Z) plays a significant role in the north-western part of Tibet. It corresponds to the following horizontal zones of vegetation from south-east to north-west: montane forest - alpine meadow - alpine steppe - alpine desert. An example on the southern slopes of the Eastern Himalayas has been taken to investigate the vertical variation of the spectra of floristic elements. The boundary between the both sub-belts of the montane evergreen broad-leafed forest belt - at an elevation of 1,800 m - has been proposed as the upper limit dominated by the tropical geo-element. On the basis of dominance spectra of the floristic elements in the grid-square system floristic boundaries are defined, which separate different floristic regions from one another; thereafter a floristic division of Tibet is discussed. There are the sub-region of the Himalayan flanks belonging to the Indo-Malaysian sub-kingdom of the Palaeo-tropical kingdom, the Sino-Himalayan region and the Tibetan Plateau region of the Holarctic kingdom. As a whole, the Tibetan Plateau may be considered as a floristic region under the Holarctic kingdom, lawing a young and derivative flora, and a close connection with the neighbouring regions.